Pemberdayaan Perempuan Melalui Program Keluarga Harapan di Kabupaten Klaten (Studi Gender Model Sara Hlupekile Longwe) - Anisa Desianti Ramadhani; Sri Yuliani (Jurnal Mahasiswa Wacana Publik, 2022)
Poverty is a global issue and is included in the agenda of the Sustainable Development Goals (SDGs). According to Whitehead (Kemenpppa. 2016) conducted a data collection that more than half of the poor in developing countries are women. Klaten Regency is one of the regencies with a Gender Development Index which continues to increase in 2018- 2020. However, based on the per capita expenditure data of Klaten Regency, it shows that women's per capita expenditure is lower than that of men in Klaten Regency, this shows that there is still a gender gap in the level of women's economic welfare which is lower than that of men in Klaten Regency. tackling poverty as well as efforts to accommodate women's empowerment, namely by running the Family Hope Program. The theory used in this study is Sara Hlupekile Longwe's women's empowerment framework theory: namely: welfare, access, awareness, participation, and control. In this study, the method used is descriptive qualitative research method where the data collection techniques used are interview techniques and documentation studies. The field findings show that although the empowerment of women in the Family Hope Program has been able to increase the level of welfare, access, awareness and participation, it has not been able to reach the level of control. This shows that the empowerment of women in the Family Hope Program has not been fully empowered. This situation is influenced by several factors, one of which is patriarchal culture which still affects people's lives.